HYDATID CYSTS OF THE BRAIN - Ali, Mumtaz; Mahmood, Khalid; Khan, Pervez (Journal of Ayub Medical College Abbottabad, 2009)
Background: Brain involvement with hydatid disease occurs in 1-2% of all Echinococcus granulosus infections. Cerebral hydatid cysts are usually supratentorial, whereas infratentorial lesions are quite rare. Objective of the study was to determine the clinical presentation and surgical outcome of cranial hydatidosis. Methods: This retrospective study was performed in the department of neurosurgery LRH Peshawar from December 2000 to Oct 2007. Twenty one cases with intracranial hydatidosis were operated. The patients were either admitted through OPD or referred from other units. CT and/or MRI were the imaging modalities to reach the diagnosis in addition to serological and haematological tests. Surgery was the only treatment option used. Pericystic hydraulic method was the technique used for the excision of the hydatid cyst of brain. Results: There were 9 males and 12 females with male to female ratio of 1:1.3. All patients belonged to paediatric age group with age range of 3-14 years and mean age of 7.42±3.2 years. Headache, vomiting, papilloedema were present in all the patients while seizures were the present in 16 patients. The lesion was removed surgically by adopting pericystic hydraulic method during craniotomy in all cases. There was no intra-operative morbidity except that the cyst ruptured in one case. No postoperative complications were noted and there was no mortality. Conclusion: Hydatid cyst of the brain presents clinically as intracranial space occupying lesion and is more common in children. Surgery is the treatment option with affordable morbidity and low mortality. Keywords: Cerebral hydatid cyst, Echinococcosis, Intracranial hydatidosis